Literature Review: Relationship Between Physical Activities, Eating Habits, Body Image, Nutritional Status With Adolescent Achievement - Winda Saukina Syarifatul Jannah; Fauzie Rahman; Muhammad Irwan Setiawan (Jurnal Publikasi Kesehatan Masyarakat Indonesia, 2022)
The Nutritional Status Monitoring (NSM) 2017 percentage data shows severely underweight and underweight school students and adolescents aged 16-18 years based on the BMI/U index in Indonesia was 0.9% severely underweight and 3.0% underweight. Meanwhile, the percentage of nutritional status of adolescent girls aged 12-18 years is 1.2% severely underweight, 3.5% underweight, 75.8% normal, 15.1% overweight, and 4.3% obese. The Ministry of Education data from the 2017/2018 academic year regarding Vocational High Schools (VHS) learning achievement in 34 provinces throughout Indonesia, it was recorded that there were 13,665 of 4,899,136 students who doing remedial. According to the WHO data in 2005, adolescent nutritional status is influenced by physical activity, eating habits, and body image, which will have an impact on adolescent learning achievement. This research aimed to examine articles related to the relationship between physical activity, eating habits, body image, nutritional status, and achievement in adolescents. This research is a literature review type with scoping review method. The keywords namely physical activity, eating habits, body image, nutritional status, and achievement of academic adolescents. Research articles/data were obtained through Google Scholar, DOAJ, and Springer. 11 research articles fit the inclusion criteria. From the analysis, it was found that physical activity, eating habits, body image, and nutritional status had a relationship with adolescent achievement.